Principal Policy in Developing Islamic Student Characters - Tanzeh, Ahmad; Junaris, Imam (The Pontianak State Institute of Islamic Studies, 2019)
A principal has an important role in establishing student character because a principal is authorized to put policies and rules related to the development of educational institutions. The principal rule is to lead, to guide and to counsel the teachers and staff, so that they can carry out their duties properly. The teacher as an educator and facilitator is an extension of the principal in developing student character. The phenomenon of juvenile delinquency occurred recently is a proof that at this time the spiritual mentality of young generation still weak. Therefore, it is very important to encourage religious values, character and cultural building to the students at the early stage/age.